Mobile application for thermal design of helixchanger heat exchangers - Ter, Owen Guowen (2016)
A mobile-based application was developed for the design of Shell-and-Tube Heat Exchangers with helical baffles, also known as Helixchangers. The application was developed only for the Android operating system which accounts for 84% of smartphone users worldwide. Helixchangers are rarely reported in the open literature and therefore are difficult for students and practising engineers to learn how to design. An alternative, modified version of the well-established Bell-Delaware and Kern methods is used for this project to size Helixchangers. The application provides the user a choice of either “learner” or “advanced” modes. The “learner” mode provides an easy to follow step-by-step guide for the user to learn the basic concept of a Helixchanger heat exchanger. The “advanced” mode is a one-page interface where the user keys in the input values to get the results instantaneously. The results from the application have been validated by manual calculation and found to be rather accurate.